Teacher education for cultural diversity - Maged, Shireen (Curtin University, 2011)
The rapidly growing cultural diversity of school children is an international trend that has been accompanied by concerns that teacher education programmes are not adequately preparing pre-service teachers for culturally diverse classrooms. This qualitative instrumental case study was conducted to gain deep insights into how one teacher education programme at a New Zealand university prepared pre-service teachers for cultural diversity. The study was conceptualised, conducted and analysed through a critical constructivist lens and underpinned by Vygotskian sociocultural theory. The primary research question asked: In what ways are New Zealand pre-service teachers prepared to meet the learning needs of students in culturally diverse classrooms? The question was explored on four levels: Curriculum, pedagogy, perceptions of effectiveness and diversity capacity. Data were collected using semi-structured interviews, observation, document analysis and field notes and were thematically analysed and interpreted through deductive and inductive coding.Results were reported thematically and reflected multiple layers of meaning and interpretations emphasising the complexity of the issue. Key curriculum findings revealed variability in the depth of pre-service teacher preparation for cultural diversity and a predominantly conceptual development of sociocultural competence. The pedagogical findings reported on three types of pedagogical activity, namely dialogic activity, monologic activity and reflective activity and four types of social relationships, namely expert-novice, professional partnership, critical minority and silent minority. Additionally, findings on participant perceptions of effectiveness and on the impact of the teacher’s cultural background on teaching and learning are detailed. The study makes three propositions on how to prepare pre-service teachers for cultural diversity. Limitations of the study and directions for future research are outlined.